Ontogeny of morningness-eveningness across the adult human lifespan - Randler, Christoph (The Science of nature, 2016)
Sleep timing of humans can be classified alongside a continuum from early to late sleepers, with some people (larks) having an early activity, early bed, and rise times and others (owls) with a more nocturnally orientated activity. Only a few studies reported that morningness-eveningness changes significantly during the adult lifespan based on community samples. Here, I applied a different methodological approach to seek for evidence for the age-related changes in morningness-eveningness preferences by using a meta-data from all available studies. The new aspect of this cross-sectional approach is that only a few studies themselves address the age-related changes of the adult lifespan development, but that many studies are available that provide exactly the data needed. The studies came from 27 countries and included 36,939 participants. Age was highly significantly correlated with scores on the Composite Scale of Morningness (r = 0.70). This relationship seems linear, because a linear regression explained nearly the same amount of variance compared to other models such as logarithmic, quadratic, or cubic models. The standard deviation of age correlated with the standard deviation of CSM scores (r = 0.55), suggesting when there is much variance in age in a study; in turn, there is much variance in morningness. This meta-analytical approach shows that morningness-eveningness changes across the adult lifespan and that older age is related to higher morningness.
Published online: 29 December 2015
Gesehen am 17.02.2021